2008
DOI: 10.1177/0146167208319385
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Positive Mood Buffering Among College Student Drinkers

Abstract: Positive experiences play an important role in buffering the effects of negative experiences. Although this process can play out in a myriad of contexts, the college context is one of particular importance because of significant concerns about student stress levels and alcohol abuse. Building on evidence that at least some students drink in response to negative experiences, we considered the possibility that positive moods would moderate college student negative mood-drinking relationships. Using a Web-based d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 35 publications
7
49
0
Order By: Relevance
“…Potential candidates are stress-induced consumption behaviours such as alcohol intake (Mohr, Brennan, Mohr, Armeli, & Tennen, 2008;Sher & Grekin, 2007;Zack, Poulos, Fragopoulos, Woodford, & MacLeod, 2006) and smoking (Gilbert et al, 2007). Other bodily emotion-regulation strategies that may be at least partly needoriented are regular physical exercise, particularly when people have developed exercise habits (Thayer, 1987), and stress-induced proximity seeking, particularly among women (Taylor et al, 2000).…”
Section: The Psychology Of Emotion Regulation 19mentioning
confidence: 99%
“…Potential candidates are stress-induced consumption behaviours such as alcohol intake (Mohr, Brennan, Mohr, Armeli, & Tennen, 2008;Sher & Grekin, 2007;Zack, Poulos, Fragopoulos, Woodford, & MacLeod, 2006) and smoking (Gilbert et al, 2007). Other bodily emotion-regulation strategies that may be at least partly needoriented are regular physical exercise, particularly when people have developed exercise habits (Thayer, 1987), and stress-induced proximity seeking, particularly among women (Taylor et al, 2000).…”
Section: The Psychology Of Emotion Regulation 19mentioning
confidence: 99%
“…Shame is more common among those with substance use problems than those without such problems (Cook, 1987; Dearing et al, 2005), evokes substance use (e.g., Mohr, Brannan, Mohr, Armeli, & Tennen, 2008), and predicts relapse during Alcoholics Anonymous participation (Wiechelt & Sales, 2001). Shame is also the emotional core of self-stigma, which has been associated with treatment-seeking delays (Kushner & Sher, 1991), treatment dropout (Sirey et al, 2001), and poorer social functioning (Perlick et al, 2001).…”
mentioning
confidence: 99%
“…A number of human studies highlight the importance of developing positive coping strategies-such as family dinners, mindfulness training, positive thinking-for successful treatment and prevention of alcoholism and addiction (Brady et al 2009;Daeppen et al 2010;Franko et al 2008;Fulkerson et al 2006;Mohr et al 2008;Pohorecky 1991;Volkow et al 2010;Wang et al 2009). Furthermore, inasmuch as addicts and posttraumatic stress disorder patients often exhibit an inability to tolerate distress (Daughters et al 2009;Howell et al 2010;Marinkovic et al 2009), studies have shown that they can reduce their alcohol intake by learning strategies to cope with stress (Armeli et al 2010;Daeppen et al 2010;Fulkerson et al 2006;Garland et al 2010;Mohr et al 2008;Pohorecky 1991;Vieten et al 2010).…”
Section: Positive Coping Strategiesmentioning
confidence: 99%
“…Furthermore, inasmuch as addicts and posttraumatic stress disorder patients often exhibit an inability to tolerate distress (Daughters et al 2009;Howell et al 2010;Marinkovic et al 2009), studies have shown that they can reduce their alcohol intake by learning strategies to cope with stress (Armeli et al 2010;Daeppen et al 2010;Fulkerson et al 2006;Garland et al 2010;Mohr et al 2008;Pohorecky 1991;Vieten et al 2010).…”
Section: Positive Coping Strategiesmentioning
confidence: 99%
See 1 more Smart Citation